USO DE BAUHINIA FORFICATA COMO FORMA COMPLEMENTAR NO TRATAMENTO DE DIABETES MELLITUS - Petri, Aniele A.; Dalpiaz, Jaqueline; Schiavo, Morgana; Spanevello, Stella; Camillo, Verônica N.; Colet, Christiane F. (Salão do Conhecimento, 2013)
Resumo